Placental Allograft Reconstruction of Cutaneous Wounds Following Mohs Surgery: A Propensity Score-Matched Comparative Cost-Effectiveness Analysis - Toman, Julia; Adams, John R; Choi, Melanie; Mason, David; Hubbs, Brandon S; Forsyth, R Allyn; Rogers, Gary S (Journal of drugs in dermatology, 2025)
The purpose of this study was to examine the cost-effectiveness of placental allograft as a nonoperative surrogate to autologous tissue-based methods of defect reconstruction on the face, head, and dorsal hand following Mohs micrographic surgery (MMS). This study was a 5-year retrospective, analysis comparing propensity-matched cohorts of eligible Mohs surgery patients treated with a placental allograft (dHACM, dehydrated human amnion/chorion membrane) vs autologous tissue-based repairs. Costs on day 0 through discharge were used for a cost-effectiveness analysis (CEA) and an incremental cost-effectiveness ratio (ICER). Four-hundred-twenty-nine propensity-matched patients meeting the entry/exclusion criteria were divided into treatment (dHACM) and Standard of Care (SOC) cohorts in a 1:2 match. The study population was 78.8% male, with a mean age of 77.8 ± 9.3 years. The primary reconstruction cost increased with dHACM (P<.0001), while the cumulative cost of care was similar between groups (P>0.05). MMS defects treated with dHACM had significantly lower rates of adverse post-repair sequelae; infection (P=0.0114), dehiscence (P=0.0189), necrosis (P=0.0349), hematoma (P=0.0066) and scar revisions (P=0.0044), resulting in an average savings of $409.55 for high-risk post-MMS defects and a dominant ICER. In subjects meeting the entry/exclusion criteria, closure of post-MMS defects with dHACM resulted in significantly lower rates of adverse post-repair sequelae (2.8% vs 21.3%, P<.0001), which offset the upfront cost of dHACM, resulting in shorter lengths of care and favorable cosmetic outcomes. dHACM may be a cost-effective approach for surgical wounds in select patient populations. Toman J, Adams JR, Choi M, et al. Placental allograft reconstruction of cutaneous wounds following Mohs surgery: a propensity score-matched comparative cost-effectiveness analysis. J Drugs Dermatol. 2025;24(5):450-456. doi:10.36849/JDD.8436.